Rotigotine patches (Neupro) in early Parkinson’s disease - Sacchi, Viola (Farmeconomia. Health Economics and Therapeutic Pathways, 2008)
Parkinson’s disease (PD) is a neurodegenerative disorder secondary to the progressive loss of dopaminergic neurons in the substantia nigra (a portion of the midbrain responsible for movement initiation and coordination) and appearance of bradykinesia, resting tremor, rigidity and postural reflex impairment. The most common symptomatic therapy is levodopa, a dopamine precursor; however, long-term treatment leads to involuntary movements and response fluctuations which add to the complexities of later disease-management. Monotherapy with dopamine agonists may represent an alternative approach with a reduced likelihood of motor complications; these drugs, initially introduced as adjunctive therapy to levodopa, are less effective in controlling motor disability and tend to cause more sideeffects than levodopa itself.